Analysis of the adiponectin paradox in healthy older people - Carina O. Walowski; Catrin Herpich; Janna Enderle; Wiebke Braun; Marcus Both; Mario Hasler; Manfred J. Müller; Kristina Norman; Anja Bosy‐Westphal (Journal of Cachexia, Sarcopenia and Muscle, 2023)
Abstract Background It remains unknown why adiponectin levels are associated with poor physical functioning, skeletal muscle mass and increased mortality in older populations. Methods In 190 healthy adults (59–86 years, BMI 17–37 kg/m2, 56.8% female), whole body skeletal muscle mass (normalized by height, SMI, kg/m2), muscle and liver fat were determined by magnetic resonance imaging. Bone mineral content (BMC) and density (BMD) were assessed by dual X‐ray absorptiometry (n = 135). Levels of insulin‐like growth factor 1 (IGF‐1), insulin, inflammation markers, leptin and fibroblast growth factor 21 were measured as potential determinants of the relationship between adiponectin and body composition. Results Higher adiponectin levels were associated with a lower SMI (r = −0.23, P < 0.01), BMC (r = −0.17, P < 0.05) and liver fat (r = −0.20, P < 0.05) in the total population and with higher muscle fat in women (r = 0.27, P < 0.01). By contrast, IGF‐1 showed positive correlations with SMI (r = 0.33), BMD (r = 0.37) and BMC (r = 0.33) (all P < 0.01) and a negative correlation with muscle fat (r = −0.17, P < 0.05). IGF‐1 was negatively associated with age (r = −0.21, P < 0.01) and with adiponectin (r = −0.15, P < 0.05). Stepwise regression analyses revealed that IGF‐1, insulin and leptin explained 18% of the variance in SMI, and IGF‐1, leptin and age explained 16% of the variance in BMC, whereas adiponectin did not contribute to these models. Conclusions Associations between higher adiponectin levels and lower muscle or bone mass in healthy older adults may be explained by a decrease in IGF‐1 with increasing adiponectin levels.